Optical fiber embedded flexible wiring board and method for manufacturing the same
Patent Information
- Application Number
- CN202611412694.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-11
- Publication Date
- 2026-10-13
AI Technical Summary
[0005]针对现有FPC的光纤埋置易受热压影响偏移走位和断裂的问题,本发明提供了一种光纤埋入柔性线路板及其制备方法
[0015]根据本发明提供的光纤埋入柔性线路板,采用芯层高Tg刚性支撑、表层低Tg熔融粘结的分层功能设计,通过功能分层的结构同时满足高温层压下的光纤防护与基板粘结需求。聚丙烯酸酯芯层的玻璃化转变温度高于柔性线路板常规热压层压温度,层压过程中芯层始终保持玻璃态,分子链段运动被交联网络严格限制,具备稳定的结构强度与抗压缩能力,可将层压压力均匀分散至整个芯层平面,避免压力直接集中作用于光纤表面,降低纤芯受压断裂、光纤偏移走位的风险。两侧的第一聚丙烯酸酯表层与第二聚丙烯酸酯表层玻璃化转变温度低于层压温度,热压过程中表层树脂处于高弹-粘流过渡态,可充分浸润第一柔性子板层、第二柔性子板层的表面微观凹凸结构,形成牢固的界面粘结;同时表层熔体具备合适的内聚强度,不会发生过度流淌,避免树脂流失导致的胶层厚度不均与芯层移位。
Smart Images

Figure CN122909765A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of flexible circuit board technology, specifically relating to an optical fiber embedded flexible circuit board and its preparation method. Background Technology
[0002] With the rapid development of 5G communications, high-speed data centers, and foldable consumer electronics, the signal transmission rate on flexible printed circuit boards (FPCs) continues to increase. Traditional copper-based electrical interconnects are gradually showing inherent bottlenecks in high-speed scenarios, such as large signal attenuation, severe crosstalk, and prominent electromagnetic interference (EMI) problems, making it difficult to meet the high-speed interconnect requirements of hundreds of Gbps and above. Against this backdrop, embedded fiber optic communication solutions, which use optical fibers as the optical interconnect medium embedded inside FPCs to replace part of the high-speed electrical signals for transmission, have become an important development direction in the field of high-speed flexible interconnects due to their significant advantages such as high bandwidth, low loss, resistance to electromagnetic interference, and light weight.
[0003] Currently, the embedding of optical fibers in FPCs mainly adopts the process route of interlayer adhesive film encapsulation and fixation: the optical fiber is placed in the interlayer adhesive film of the FPC, and the adhesive film is cured and bonded by hot pressing, thus encapsulating and fixing the optical fiber inside the flexible substrate. Among them, polyacrylate film is the mainstream adhesive film material for interlayer bonding and optical fiber embedding in FPCs due to its excellent adhesion to polyimide (PI) substrate, good film-forming properties, good weather resistance, and wide processing window.
[0004] However, existing conventional polyacrylate films have significant technical drawbacks when applied to embedded fiber optic FPCs: to ensure the film's wetting adhesion and leveling filling ability to the substrate during hot pressing, the glass transition temperature of existing polyacrylate films is usually low. Under the temperature conditions of FPC hot pressing lamination, the film is in a viscous flow state, with low melt strength and weak compression resistance, failing to provide effective rigid protection for the embedded optical fiber. During hot pressing, the lamination pressure acts directly on the fiber surface through the flowing film, and the molten resin also generates lateral shear force on the fiber, causing localized stress concentration. This easily leads to problems such as fiber core breakage, fiber misalignment, and a significant increase in microbending loss, ultimately resulting in product optical performance failure, low production yield, and poor long-term reliability. Summary of the Invention
[0005] To address the problem that optical fiber embedding in existing FPCs is susceptible to displacement and breakage due to thermal pressure, this invention provides an optical fiber embedded flexible circuit board and its fabrication method.
[0006] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows: On one hand, the present invention provides an optical fiber embedded flexible circuit board, comprising a first flexible sub-board layer, a second flexible sub-board layer, and a composite polyacrylate film. The composite polyacrylate film is located between the first flexible sub-board layer and the second flexible sub-board layer. A first circuit layer is disposed on the surface of the first flexible sub-board layer facing the composite polyacrylate film, and a second circuit layer is disposed on the surface of the second flexible sub-board layer facing the composite polyacrylate film. The composite polyacrylate film comprises an optical fiber, a polyacrylate core layer, a first polyacrylate surface layer, and a second polyacrylate surface layer. The polyacrylate core layer is film-shaped, and the optical fiber is embedded in the polyacrylate core layer. The first polyacrylate surface layer... The first polyacrylate surface layer and the second polyacrylate surface layer are respectively located on both sides of the polyacrylate core layer. The glass transition temperature of the polyacrylate core layer is 165℃~178℃, the glass transition temperature of the first polyacrylate surface layer is 112℃~125℃, and the glass transition temperature of the second polyacrylate surface layer is 112℃~125℃. The polyacrylate core layer is formed by emulsion polymerization of monomer components comprising the following parts by weight, followed by thermal crosslinking and curing: 58~72 parts of high Tg hard monomer, 8~15 parts of acrylonitrile, 2~5 parts of 1,6-hexanediol dimethacrylate, 4~8 parts of epoxy functional monomer, 3~6 parts of carboxyl functional monomer, 2~4 parts of silane coupling monomer, and 2~4 parts of fluorine-containing monomer. The high Tg hard monomer includes one or more of isoborneol methacrylate and cyclohexyl methacrylate; the epoxy functional monomer is selected from glycidyl methacrylate; the carboxyl functional monomer is selected from methacrylic acid; the silane coupling monomer is selected from γ-methacryloyloxypropyltrimethoxysilane; and the fluorine-containing monomer is selected from hexafluorobutyl methacrylate.
[0007] Optionally, the optical fiber includes a core and a cladding, the cladding covering the outer periphery of the core, the core being phosphorus-doped quartz, the cladding being fluorine-doped quartz, the diameter of the core being 10~70μm, and the thickness of the cladding being 20~60μm.
[0008] Optionally, the first polyacrylate surface layer and the second polyacrylate surface layer are each independently polymerized from monomer components comprising the following parts by weight: 45-55 parts of methyl methacrylate, 35-42 parts of isoborneol methacrylate, 3-6 parts of n-butyl acrylate, 4-6 parts of hydroxyethyl methacrylate, 2-4 parts of acrylic acid, and 0.5-1.5 parts of trimethylolpropane triacrylate.
[0009] Optionally, the thickness of the polyacrylate core layer is 100~300μm; the thickness of the first polyacrylate surface layer and the second polyacrylate surface layer are each 15~50μm; the optical fibers are arranged in a parallel array within the polyacrylate core layer, and the channel spacing between adjacent optical fibers is 127~5000μm.
[0010] Optionally, the composite polyacrylate film further includes an elastic metal sheet, which is embedded in the polyacrylate core layer in parallel with the optical fiber, and the length direction of the elastic metal sheet is parallel to the extension direction of the optical fiber. The optical fiber embedded in the flexible circuit board has an electrical connection hole that penetrates the first flexible sub-board layer, the composite polyacrylate film, and the second flexible sub-board layer. The electrical connection hole avoids the optical fiber and the elastic metal sheet and electrically connects the first circuit layer and the second circuit layer.
[0011] Furthermore, the present invention provides a method for fabricating an optical fiber embedded in a flexible circuit board as described above, comprising the following steps: S1. Polyacrylate core layer emulsion was prepared by semi-continuous seed emulsion polymerization. S2. Coat the release carrier surface with a polyacrylate core layer emulsion and semi-dry it with hot air to form a semi-dry base film; arrange the optical fibers in parallel on the surface of the semi-dry base film, then coat the optical fibers with a polyacrylate core layer emulsion to completely wrap the optical fibers, and pre-cur them after drying to obtain the polyacrylate core layer of the embedded optical fiber. S3. Coat the upper and lower surfaces of the polyacrylate core layer with polyacrylate surface emulsion, and dry with hot air to form a film to obtain a composite polyacrylate film. S4. The composite polyacrylate film is placed between the first flexible sub-board layer with the first circuit layer and the second flexible sub-board layer with the second circuit layer, and then placed in a laminator for heating and pressing to cure. After cooling, an optical fiber embedded flexible circuit board is obtained.
[0012] Optionally, step S1 specifically includes: Dissolve the emulsifier in deionized water and stir until completely dissolved; mix the high Tg hard monomer, acrylonitrile, 1,6-hexanediol dimethacrylate, epoxy functional monomer, carboxyl functional monomer and fluorine-containing monomer evenly and slowly add them to the emulsifier aqueous solution, and disperse at high speed to obtain a pre-emulsion with a solid content of 42%~45%. Add water, 10%~20% pre-emulsion and 20%~30% initiator aqueous solution to the reaction vessel, stir and heat to 78℃, keep the temperature for 20~40 min to generate seed emulsion; Maintain the reaction temperature at 80-82℃, and simultaneously and uniformly add the remaining pre-emulsion and the remaining initiator aqueous solution for 3.5-5 hours; after the addition is complete, add the silane coupling monomer to the system. After completion, heat to 85℃~90℃ and maintain for 1.5~3 hours, then cool to below 40℃, adjust pH to 6.0~6.5, and filter to obtain polyacrylate core layer emulsion.
[0013] Optionally, in step S3, the polyacrylate surface emulsion is prepared by a semi-continuous seed emulsion polymerization method, with a solid content of 38%~42%; after coating, it is dried with hot air at 80~100℃ to remove moisture.
[0014] Optionally, in step S4, the lamination pressure is controlled at 15~25 bar and the temperature is 150℃~160℃.
[0015] The fiber-embedded flexible circuit board provided by this invention adopts a layered functional design with a high-Tg rigidity support core layer and a low-Tg fusion bonding surface layer. This layered structure simultaneously meets the requirements for fiber protection and substrate bonding under high-temperature lamination. The glass transition temperature of the polyacrylate core layer is higher than the conventional hot-pressing lamination temperature of flexible circuit boards. During lamination, the core layer remains in a glassy state, and the movement of molecular chain segments is strictly restricted by the cross-linked network, resulting in stable structural strength and compression resistance. This allows the lamination pressure to be evenly distributed across the entire core layer plane, avoiding direct pressure concentration on the fiber surface and reducing the risk of core breakage and fiber displacement. The glass transition temperatures of the first and second polyacrylate surface layers on both sides are lower than the lamination temperature. During hot pressing, the surface resin is in a highly elastic-viscosity transition state, which can fully wet the micro-uneven surface structure of the first and second flexible sub-layers, forming a strong interfacial bond. Simultaneously, the surface melt possesses suitable cohesive strength, preventing excessive flow and avoiding uneven adhesive layer thickness and core layer displacement caused by resin loss. Attached Figure Description
[0016] Figure 1 This is a schematic diagram of the structure of the optical fiber embedded in the flexible circuit board provided by the present invention; Figure 2 This is a schematic diagram of the polyacrylate core layer of the embedded optical fiber provided in step S2 of the preparation method of the present invention; Figure 3 This is a schematic diagram of the structure of the composite polyacrylate film provided in step S3 of the preparation method of the present invention; Figure 4 This is a schematic diagram of the laminated structure provided in step S4 of the preparation method of the present invention.
[0017] The reference numerals in the accompanying drawings are as follows: 1. First flexible sub-board layer; 11. First circuit layer; 2. Second flexible sub-board layer; 21. Second circuit layer; 3. Composite polyacrylate film; 31. Polyacrylate core layer; 32. First polyacrylate surface layer; 33. Second polyacrylate surface layer; 4. Electrical connection hole; 5. Optical fiber; 51. Fiber core; 52. Cladding; 6. Elastic metal sheet; 7. Release carrier. Detailed Implementation
[0018] To make the technical problems solved, the technical solutions, and the beneficial effects of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.
[0019] See Figure 1 As shown, an embodiment of the present invention provides an optical fiber 5 embedded in a flexible circuit board, including a first flexible sub-board layer 1, a second flexible sub-board layer 2, and a composite polyacrylate film 3. The composite polyacrylate film 3 is located between the first flexible sub-board layer 1 and the second flexible sub-board layer 2. A first circuit layer 11 is disposed on the surface of the first flexible sub-board layer 1 facing the composite polyacrylate film 3, and a second circuit layer 21 is disposed on the surface of the second flexible sub-board layer 2 facing the composite polyacrylate film 3. The composite polyacrylate film 3 includes an optical fiber 5, a polyacrylate core layer 31, and a first circuit layer 11. The polyacrylate surface layer 32 and the second polyacrylate surface layer 33 are respectively located on the two sides of the polyacrylate core layer 31. The glass transition temperature of the polyacrylate core layer 31 is 165℃~178℃, the glass transition temperature of the first polyacrylate surface layer 32 is 112℃~125℃, and the glass transition temperature of the second polyacrylate surface layer 33 is 112℃~125℃.
[0020] The glass transition temperature of the polyacrylate core layer 31 is higher than that of the conventional hot-pressing lamination temperature for flexible circuit boards. During the lamination process, the core layer remains in a glassy state, and the movement of molecular chain segments is strictly restricted by the cross-linked network, resulting in stable structural strength and compressive strength. This allows the lamination pressure to be evenly distributed across the entire core layer plane, preventing pressure from being directly concentrated on the surface of the optical fiber 5 and reducing the risk of core 51 breaking under pressure and optical fiber 5 shifting. The glass transition temperatures of the first polyacrylate surface layer 32 and the second polyacrylate surface layer 33 on both sides are lower than the lamination temperature. During the hot pressing process, the surface resin is in a high-elasticity-viscosity transition state, which can fully wet the micro-uneven surface structure of the first flexible sub-layer 1 and the second flexible sub-layer 2, forming a strong interfacial bond. At the same time, the surface melt has suitable cohesive strength and will not flow excessively, avoiding uneven adhesive layer thickness and core layer displacement caused by resin loss.
[0021] The polyacrylate core layer 31 forms a chemical bond with the first polyacrylate surface layer 32 and the second polyacrylate surface layer 33 through the reaction of interfacial functional groups, without physical layering interface. The overall structure simultaneously achieves high-temperature optical fiber 5 protection and interfacial bonding, avoiding the problem that the adhesion decreases when the Tg of a single-layer adhesive film is increased, and the fiber protection is insufficient when the Tg is decreased.
[0022] The glass transition temperature of the polyacrylate core layer 31 is controlled between 165℃ and 178℃. Specific values within this range include: 165℃, 166℃, 167℃, 168℃, 169℃, 170℃, 171℃, 172℃, 173℃, 174℃, 175℃, 176℃, 177℃, and 178℃, with the preferred range being 168℃ to 175℃. If the glass transition temperature is below 165℃, the polyacrylate core layer 31 approaches or enters the glass transition region during lamination, increasing the mobility of molecular chain segments and significantly reducing structural strength and compressive strength. This makes it impossible to effectively disperse lamination pressure, and the optical fiber 5 still faces the risk of breakage under pressure. If the glass transition temperature is above 178℃, the cross-linking density of the core layer is too high, significantly increasing the resin's brittleness. Under the bending conditions of the flexible circuit board, cracks are easily generated, which can damage the internal optical fiber 5. At the same time, the curing difficulty increases, and the production cycle is prolonged.
[0023] The glass transition temperatures of the first polyacrylate surface layer 32 and the second polyacrylate surface layer 33 are controlled between 112℃ and 125℃. Specific values within this range include 112℃, 114℃, 116℃, 118℃, 120℃, 122℃, 124℃, and 125℃, with the preferred range being 116℃ to 122℃. If the glass transition temperature is below 112℃, the viscosity of the surface resin melt is too low during lamination, resulting in excessive fluidity and problems such as excessive resin flow and uneven adhesive layer thickness. If the glass transition temperature is above 125℃, the surface resin melt is insufficient during lamination, leading to insufficient wettability to the flexible substrate, reduced interfacial bonding strength, and a tendency for interlayer delamination defects to occur.
[0024] The glass transition temperature was measured using dynamic thermomechanical analysis (DMA), with the peak temperature of the loss factor tanδ as the glass transition temperature. The test frequency was 1 Hz and the heating rate was 5 °C / min.
[0025] In some embodiments, the polyacrylate core layer 31 is formed by emulsion polymerization and then thermal crosslinking and curing of monomer components comprising the following parts by weight: 58-72 parts of high Tg hard monomer, 8-15 parts of acrylonitrile, 2-5 parts of 1,6-hexanediol dimethacrylate, 4-8 parts of epoxy functional monomer, 3-6 parts of carboxyl functional monomer, 2-4 parts of silane coupling monomer, and 2-4 parts of fluorine-containing monomer; wherein, the high Tg hard monomer includes one or more of isobornyl methacrylate and cyclohexyl methacrylate; the epoxy functional monomer is selected from glycidyl methacrylate; the carboxyl functional monomer is selected from methacrylic acid; the silane coupling monomer is selected from γ-methacryloyloxypropyltrimethoxysilane; and the fluorine-containing monomer is selected from hexafluorobutyl methacrylate.
[0026] High-Tg hard monomers provide the core layer with fundamental rigidity and intrinsic glass transition temperature. In a preferred embodiment, isobornyl methacrylate and cyclohexyl methacrylate are mixed as high-Tg hard monomers. Isobornyl methacrylate, with its large-volume alicyclic isobornyl group, exhibits strong steric hindrance, and its homopolymer glass transition temperature is approximately 170°C, making it the core source of the high Tg of the core layer. Simultaneously, its alicyclic structure results in low water absorption, improving the film's resistance to damp heat. Cyclohexyl methacrylate, with its cyclohexyl structure, is less rigid than isobornyl but has greater molecular chain mobility, used to adjust the system's toughness and prevent excessive embrittlement of the pure isobornyl methacrylate system. The combination of these two monomers allows for wide-range control of the core layer's fundamental Tg and toughness balance. The dosage of high-Tg hard monomers should be controlled between 58 and 72 parts by weight. Specific values within this range include: 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, and 72 parts by weight, with the preferred range being 62 to 68 parts by weight. When the dosage is below 58 parts by weight, the system's basic rigidity is insufficient, and the final Tg after crosslinking is difficult to reach above 165°C, resulting in insufficient high-temperature compressive strength. When the dosage is above 72 parts by weight, the system's hardness is too high, and the brittleness after curing increases significantly, making it prone to cracking during bending.
[0027] Acrylonitrile is a highly polar monomer. The dipole-dipole interaction of the cyano group can significantly enhance the cohesive force between molecular chains, helping to improve the Tg and structural strength of the system. Simultaneously, the polar groups can enhance the interfacial interaction between the resin and the surface of optical fiber 5, as well as the surface resin. Its dosage is controlled between 8 and 15 parts by mass. Specific values within this range include 8, 9, 10, 11, 12, 13, 14, and 15 parts, with the preferred range being 10 to 13 parts. When the dosage is below 8 parts, the polarity enhancement effect is insufficient, and the cohesive strength is low; when the dosage is above 15 parts, the resin's water absorption rate increases, its resistance to damp heat decreases, and the system's brittleness further increases.
[0028] 1,6-Hexanediol dimethacrylate is a long-chain bifunctional crosslinking agent that copolymerizes with double bonds to form a primary three-dimensional crosslinking network. Its 6-carbon long-chain structure provides sufficient space for movement between the crosslinking points, increasing crosslinking density while retaining a certain degree of deformability. This avoids the resin embrittlement problems caused by short-chain crosslinking agents, balancing high rigidity and moderate toughness. Its dosage is controlled between 2 and 5 parts by weight. Specific values within this range include 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, and 5.0 parts, with a preferred range of 3 to 4 parts. When the dosage is less than 2 parts, the primary crosslinking network density is insufficient, and the resin easily softens and deforms at high temperatures. When the dosage is greater than 5 parts, the crosslinking density is too high, significantly reducing resin toughness and making it prone to cracking when bent.
[0029] Epoxy and carboxyl functional monomers constitute a secondary thermal crosslinking system. These monomers copolymerize with acrylate molecules via double bonds. During the high-temperature curing stage, the epoxy and carboxyl groups undergo ring-opening addition reactions to generate ester bonds and secondary hydroxyl groups, forming a denser secondary crosslinking network. This further restricts molecular chain movement and is the core mechanism for raising the final Tg of the core layer to above 165℃. From a reaction kinetics perspective, this ring-opening reaction rate significantly accelerates above 130℃, making it suitable for segmented temperature-increasing curing processes. The crosslinking process can be precisely controlled through the curing temperature.
[0030] The amount of epoxy functional monomer is controlled between 4 and 8 parts by mass. Specific values within this range include 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, and 8 parts, with a preferred range of 5 to 7 parts. When the amount is less than 4 parts, there are insufficient sites for secondary crosslinking reactions, and the final Tg cannot meet the design requirements. When the amount is more than 8 parts, crosslinking is excessive, increasing resin brittleness and curing shrinkage, and easily introducing residual stress. The amount of carboxyl functional monomer is controlled between 3 and 6 parts by mass. Specific values within this range include 3, 3.5, 4, 4.5, 5, 5.5, and 6 parts, with a preferred range of 4 to 5 parts. When the amount is less than 3 parts, the crosslinking reaction is insufficient; when the amount is more than 6 parts, the resin polarity is too strong, and the water absorption rate increases.
[0031] The silane coupling monomer is a bifunctional interfacial bonding monomer. The double bond at one end participates in the copolymerization of acrylate and enters the resin molecular chain. The trimethoxysilyl group at the other end hydrolyzes during curing to generate silanol groups, which undergo dehydration condensation with the silanol groups on the surface of the fluorine-doped quartz cladding 52 to form stable Si-O-Si covalent bonds. This transforms the physical bonding between the resin and the cladding 52 of the optical fiber 5 into a molecular-level chemical bond, reducing the risk of interfacial delamination under temperature cycling and bending conditions. Its dosage is controlled at 2-4 parts by mass, with specific values within this range including 2.0, 2.5, 3.0, 3.5, and 4.0 parts, and the preferred range being 2.5-3.5 parts. When the dosage is less than 2 parts, the number of interfacial covalent bonds is insufficient, resulting in limited improvement in bonding strength; when the dosage is greater than 4 parts, the self-polymerization tendency of the silane monomer increases, the storage stability of the emulsion decreases, and excess silane easily accumulates at the interface, forming defects.
[0032] The fluorinated monomer, with its fluorinated side chains, reduces the surface tension of the resin system, matching the low surface energy of the fluorinated quartz cladding 52, thus improving the resin's spreading and wetting properties on the fiber 5 surface and eliminating interfacial microbubbles and micropores. Simultaneously, the fluorinated segments and the Si-F bonds of the fluorinated cladding 52 exhibit similar compatibility, strengthening the interfacial physical bond and forming a synergistic effect with the chemical bonding of the silane coupling monomer, further enhancing the interfacial bonding stability. Its dosage is controlled between 2 and 4 parts by mass, with specific values within this range including 2.0, 2.5, 3.0, 3.5, and 4.0 parts, and the preferred range being 2.5 to 3.5 parts. A dosage below 2 parts results in insufficient improvement in the spreading and wetting properties of the resin and fiber 5, leading to inadequate wetting and affecting the bonding strength between the fiber 5 and the resin, potentially causing delamination and gap problems during subsequent use. A dosage above 4 parts results in excessively low resin surface energy, weakening the interlayer bonding between the core layer and the surface resin.
[0033] Overall, the primary crosslinking network constructed from 1,6-hexanediol dimethacrylate, combined with the secondary thermal crosslinking network of epoxy-carboxyl groups, forms a dual crosslinking system, ensuring the high temperature, high Tg, and structural strength of the core layer. The molecular design of the long-chain crosslinking agent preserves toughness under high crosslinking density. Silane coupling monomers and fluorine-containing monomers address the interfacial delamination problem of fluorine-doped quartz optical fiber 5 from both chemical bonding and physical wetting perspectives. The synergistic effect of these components ensures that the core layer simultaneously meets the performance requirements of high-temperature fiber protection, bending toughness, and interfacial bonding.
[0034] In some embodiments, the first flexible sub-board layer 1 and the second flexible sub-board layer 2 are polyimide layers, and the first circuit layer 11 and the second circuit layer 21 are copper circuit layers.
[0035] In some embodiments, the optical fiber 5 includes a core 51 and a cladding 52, the cladding 52 covering the outer periphery of the core 51, the core 51 being phosphorus-doped quartz, the cladding 52 being fluorine-doped quartz, the diameter of the core 51 being 10~70μm, and the thickness of the cladding 52 being 20~60μm.
[0036] This embodiment achieves low-loss optical transmission by controlling the refractive index distribution of optical fiber 5 through doping elements. The fiber core 51 is made of phosphorus-doped quartz, which increases the refractive index of the quartz material. The cladding 52 is made of fluorine-doped quartz, which decreases the refractive index of the quartz material. Together, they form a stable step-index refractive index distribution, ensuring low-loss transmission of optical signals within the fiber core 51 via total internal reflection. Phosphorus doping also reduces the Rayleigh scattering coefficient of the quartz, further reducing the transmission loss of optical fiber 5. The fluorine-doped cladding 52 has strong chemical inertness, improving the environmental stability of optical fiber 5. The matching design of the diameter of the fiber core 51 and the thickness of the cladding 52 ensures sufficient optical transmission mode field and mechanical strength while also meeting the requirements for thinner and more flexible flexible circuit boards.
[0037] In some embodiments, the first polyacrylate surface layer 32 and the second polyacrylate surface layer 33 are each independently polymerized from monomer components comprising the following parts by weight: 45-55 parts of methyl methacrylate, 35-42 parts of isoborneol methacrylate, 3-6 parts of n-butyl acrylate, 4-6 parts of hydroxyethyl methacrylate, 2-4 parts of acrylic acid, and 0.5-1.5 parts of trimethylolpropane triacrylate.
[0038] The surface formulation is designed around the goals of precisely controlling the Tg to 112~125℃, ensuring adhesion performance, and matching the interface bonding of the core layer. It achieves a balance between melt adhesion, cohesive strength and interfacial bonding force through multi-component compounding.
[0039] Methyl methacrylate (MDMA) is the basic hard monomer, with a homopolymer Tg of approximately 105°C. It provides basic cohesive strength and structural stability, and is a fundamental component for regulating the surface Tg. Its dosage is controlled between 45 and 55 parts by mass. Specific values within this range include 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, and 55 parts, with the preferred range being 48 to 52 parts. When the dosage is below 45 parts, the system lacks rigidity, resulting in a low Tg; when the dosage is above 55 parts, the Tg is too high, and melt wettability decreases.
[0040] Isoborneol methacrylate is a high-Tg hard monomer used to precisely raise the Tg of the system to the 112-125°C range, while improving the temperature resistance and dimensional stability of the surface layer. Its dosage is controlled between 35 and 42 parts by weight, with specific values within this range including 35, 36, 37, 38, 39, 40, 41, and 42 parts, with the preferred range being 37-40 parts. When the dosage is below 35 parts, the system Tg will not reach 112°C, leading to excessive flow during lamination; when the dosage is above 42 parts, the Tg will exceed 125°C, resulting in insufficient melting and decreased adhesion.
[0041] Butyl acrylate is a soft monomer with a homopolymer Tg of approximately -55℃. Adding a small amount can improve the resin's toughness and crack resistance, avoiding the excessive brittleness of pure hard monomer systems. This makes it suitable for the bending requirements of flexible circuit boards, and its downward effect on the overall Tg is controllable. Its dosage is controlled between 3 and 6 parts by weight. Specific values within this range include 3, 3.5, 4, 4.5, 5, 5.5, and 6 parts, with the preferred range being 4 to 5 parts. When the dosage is below 3 parts, the toughening effect is not significant, and the surface layer is prone to cracking; when the dosage is above 6 parts, the Tg decreases excessively, and the lamination fluidity is too high.
[0042] Hydroxyethyl methacrylate is a hydroxyl-functionalized monomer. During high-temperature curing, the hydroxyl groups can undergo a ring-opening reaction with the residual epoxy functional groups in the core layer, forming covalent chemical bonds between the core and surface layers. This eliminates the interlayer physical interface, enhances interlayer bonding, and prevents delamination under bending and temperature cycling. Its dosage is controlled at 4-6 parts by weight, with specific values within this range including 4, 4.5, 5, 5.5, and 6 parts, with the preferred range being 4.5-5.5 parts. When the dosage is less than 4 parts, there are insufficient interfacial reaction sites, resulting in weak interlayer bonding; when the dosage is greater than 6 parts, the surface layer becomes too polar, leading to increased water absorption.
[0043] Acrylic acid is a carboxyl functional monomer. The carboxyl groups can form hydrogen bonds and van der Waals forces with polar groups on the surface of flexible substrates, significantly improving the adhesion strength of the surface layer to flexible substrates such as polyimide. It can also assist in interfacial crosslinking reactions. Its dosage is controlled between 2 and 4 parts by weight. Specific values within this range include 2, 2.5, 3, 3.5, and 4 parts, with the preferred range being 2.5 to 3.5 parts. When the dosage is less than 2 parts, the substrate adhesion is insufficient; when the dosage is more than 4 parts, the resistance to damp heat decreases.
[0044] Trimethylolpropane triacrylate is a trifunctional mild crosslinking agent used to construct a mildly crosslinked network, improving the cohesive strength and high-temperature melt viscosity of the surface layer, preventing excessive resin flow and loss during lamination, and slightly increasing the system's heat of growth (Tg), helping to precisely control the Tg within the target range. Its dosage is controlled between 0.5 and 1.5 parts by weight, with specific values within this range including 0.5, 0.7, 0.9, 1.1, 1.3, and 1.5 parts, and the preferred range being 0.8 to 1.2 parts. When the dosage is below 0.5 parts, the cohesive strength is insufficient, and resin flow is likely to occur; when the dosage is above 1.5 parts, excessive crosslinking occurs, resulting in decreased melt flowability and poor adhesion and wettability.
[0045] Overall, methyl methacrylate and isoborneol methacrylate work together to precisely control the surface Tg to the target range; n-butyl acrylate adjusts toughness to adapt to bending conditions; hydroxyethyl methacrylate and acrylic acid respectively achieve chemical bonding with the core layer and physical adhesion with the substrate; trimethylolpropane triacrylate provides mild crosslinking to balance flowability and cohesive strength. The synergistic effect of these components ensures that the surface layer possesses suitable melt flowability and bonding strength at the lamination temperature, while simultaneously forming a strong interlayer bond with the core layer.
[0046] In some embodiments, the thickness of the polyacrylate core layer 31 is 100~300μm; the thickness of the first polyacrylate surface layer 32 and the second polyacrylate surface layer 33 are each 15~50μm; the optical fibers 5 are arranged in a parallel array within the polyacrylate core layer 31, and the channel spacing between adjacent optical fibers 5 is 127~5000μm.
[0047] The thickness and spacing design balances the protection effect of fiber optic cable 5, bonding reliability, and the overall flexibility of the flexible circuit board. The polyacrylate core layer 31 is thick enough to completely encapsulate fiber optic cable 5, ensuring a uniform resin layer on both sides of fiber optic cable 5, guaranteeing even pressure distribution and avoiding localized stress concentration. The surface layer adopts a thin design, minimizing the overall film thickness while ensuring bonding strength, thereby improving the bending flexibility of the flexible circuit board. The parallel array arrangement adapts to the requirements of parallel optical interconnection, and the channel spacing covers a variety of application scenarios from high density to low density.
[0048] The thickness of the polyacrylate core layer 31 is controlled between 100 and 300 μm. Specific values within this range include 100, 120, 140, 160, 180, 200, 220, 240, 260, 280, and 300 μm, with a preferred range of 150 to 250 μm. When the thickness is less than 100 μm, the resin protective layers above and below the optical fiber 5 are too thin, resulting in limited pressure dispersion and the optical fiber 5 remaining susceptible to lamination stress. When the thickness is greater than 300 μm, the overall thickness of the adhesive film is too large, significantly reducing the bending flexibility of the flexible circuit board and increasing material costs.
[0049] The thickness of the first polyacrylate surface layer 32 and the second polyacrylate surface layer 33 is controlled within the range of 15~50μm. Specific values selectable within this range include 15, 20, 25, 30, 35, 40, 45, and 50μm, with a preferred range of 20~30μm. When the thickness is less than 15μm, the adhesive layer is too thin and cannot fully fill the micro-unevenness of the substrate surface, resulting in insufficient interfacial bonding strength. When the thickness is greater than 50μm, the amount of molten resin in the surface layer is excessive, which can easily squeeze the core layer during lamination, causing the optical fiber 5 to shift, and also reducing the overall flexibility of the adhesive film.
[0050] In some embodiments, the composite polyacrylate film 3 further includes an elastic metal sheet 6, which is embedded in the polyacrylate core layer 31 in parallel with the optical fiber 5. The length direction of the elastic metal sheet 6 is parallel to the extension direction of the optical fiber 5. The optical fiber 5 is embedded in the flexible circuit board and has an electrical connection hole 4. The electrical connection hole 4 penetrates the first flexible sub-board layer 1, the composite polyacrylate film 3, and the second flexible sub-board layer 2. The electrical connection hole 4 is arranged to avoid the optical fiber 5 and the elastic metal sheet 6. The first circuit layer 11 and the second circuit layer 21 are electrically connected by the electrical connection hole 4.
[0051] The elastic metal sheet 6 is embedded along the axial direction of the optical fiber 5 and arranged parallel to the optical fiber 5. This enhances the overall tensile and bending resistance of the core layer and disperses mechanical stress during bending. In particular, the flexible circuit board with the optical fiber 5 embedded in it provided by this invention can be bent at large arcs, but is not suitable for small arcs, as small arcs can cause the optical fiber 5 to break. By embedding the elastic metal sheet 6, the flexible circuit board with the optical fiber 5 embedded in it can maintain a large arc bending mode during bending, avoiding stress concentration during bending and further improving the reliability of the optical fiber 5. The electrical connection hole 4 penetrates through each layer to realize electrical interconnection between the upper and lower circuit layers, while avoiding the optical fiber 5 and the elastic metal sheet 6. This allows for simultaneous optical signal transmission and electrical signal transmission within the same flexible circuit board, completing optoelectronic integrated interconnection and adapting to the signal transmission requirements of high-speed systems.
[0052] Another embodiment of the present invention provides a method for fabricating an optical fiber 5 embedded in a flexible circuit board as described above, comprising the following steps: S1. Polyacrylate core layer 31 emulsion was prepared by semi-continuous seed emulsion polymerization. S2. A polyacrylate core layer 31 emulsion is coated onto the surface of the release carrier 7, and semi-dryed by hot air to form a semi-dry base film; optical fibers 5 are arranged in parallel on the surface of the semi-dry base film, and then the polyacrylate core layer 31 emulsion is coated to completely encapsulate the optical fibers 5. After drying, pre-curing is performed to obtain the following result: Figure 2 The polyacrylate core layer 31 of the embedded optical fiber 5 is shown. S3. Coat the upper and lower surfaces of the polyacrylate core layer 31 with a polyacrylate surface emulsion, and dry with hot air to form a film, to obtain the following: Figure 3 The composite polyacrylate film 3 shown; S4, such as Figure 4 As shown, the composite polyacrylate film 3 is placed between the first flexible sub-board layer 1 with the first circuit layer 11 and the second flexible sub-board layer 2 with the second circuit layer 21, and then placed in a laminator for heating and pressing curing. After cooling, the optical fiber 5 is embedded in the flexible circuit board.
[0053] This fabrication method employs a process path of first embedding fiber in the core layer, then composited with the surface layer, and finally lamination integration. The process sequence matches the functional design of the three-layer structure. First, a core layer prefabrication with embedded fiber 5 is prepared, allowing precise control over the positional accuracy and encapsulation state of fiber 5, preventing displacement during subsequent lamination. Then, the surface layer is coated on both sides of the core layer to achieve a layered functional structure; the process is simple and controllable. In the final lamination stage, the adhesive film is simultaneously cured and bonded to the substrate, making it compatible with existing flexible circuit board lamination lines without requiring large-scale equipment modifications. The entire process enables high-precision control of the fiber 5's position while ensuring the quality of the interface bonding of the three-layer structure, guaranteeing the protective effect of fiber 5 during the hot-pressing process from a process perspective.
[0054] In some embodiments, step S1 specifically includes: Dissolve the emulsifier in deionized water and stir until completely dissolved; mix the high Tg hard monomer, acrylonitrile, 1,6-hexanediol dimethacrylate, epoxy functional monomer, carboxyl functional monomer and fluorine-containing monomer evenly and slowly add them to the emulsifier aqueous solution, and disperse at high speed to obtain a pre-emulsion with a solid content of 42%~45%. Add water, 10%~20% pre-emulsion and 20%~30% initiator aqueous solution to the reaction vessel, stir and heat to 78℃, keep the temperature for 20~40 min to generate seed emulsion; Maintain the reaction temperature at 80-82℃, and simultaneously and uniformly add the remaining pre-emulsion and the remaining initiator aqueous solution for 3.5-5 hours; after the addition is complete, add the silane coupling monomer to the system. After completion, the temperature is raised to 85℃~90℃ and kept warm for 1.5~3 hours. Then, the temperature is lowered to below 40℃, the pH is adjusted to 6.0~6.5, and the material is filtered out to obtain polyacrylate core layer 31 emulsion.
[0055] The silane coupling monomer is added post-processed, after the pre-emulsion is added dropwise. This significantly reduces its residence time in the aqueous phase, avoids premature self-polymerization and deactivation, and ensures that the silane monomer is effectively integrated into the polymer molecular chain, giving full play to the interfacial bonding effect. This is a key process design to ensure the interfacial bonding force of optical fiber 5.
[0056] In some embodiments, during step S2, when arranging the optical fiber 5, an elastic metal sheet 6 is simultaneously placed on the surface of the semi-dry substrate, so that the elastic metal sheet 6 and the optical fiber 5 are arranged side by side.
[0057] In some embodiments, in step S3, the polyacrylate surface emulsion is prepared by a semi-continuous seed emulsion polymerization method, with a solid content of 38%~42%; after coating, it is dried with hot air at 80~100℃ to remove moisture.
[0058] The surface emulsion uses the same semi-continuous seed emulsion polymerization method as the core layer to ensure uniform emulsion particle size and good film-forming properties; the solid content is slightly lower than that of the core layer emulsion to meet the process requirements of thin surface coating.
[0059] In some embodiments, in step S4, the lamination pressure is controlled at 15~25 bar and the temperature is 150℃~160℃.
[0060] The lamination parameters are matched to the Tg design of the composite polyacrylate film 3. The lamination temperature is controlled between 150℃ and 160℃, with specific values within this range including 150℃, 152℃, 154℃, 156℃, 158℃, and 160℃, and the preferred range being 153℃ to 157℃. This temperature is higher than the surface layer Tg (112℃ to 125℃), allowing the surface resin to fully melt and effectively wet the flexible substrate, achieving high-strength bonding. Simultaneously, this temperature is lower than the core layer Tg (165℃ to 178℃), ensuring the core layer maintains its glassy rigidity, stably supporting the optical fiber 5 and dispersing lamination pressure. Below 150℃, the surface layer melts insufficiently, resulting in inadequate bonding strength and incomplete cross-linking of the core layer, ultimately failing to meet the design Tg requirements. Above 160℃, approaching the core layer Tg, the core layer modulus begins to decrease, weakening the support and protection capabilities, increasing the risk of pressure on the optical fiber 5, and making the flexible substrate prone to thermal deformation.
[0061] The lamination pressure is controlled between 15 and 25 bar. Specific values within this range include 15, 17, 19, 21, 23, and 25 bar, with the preferred range being 18 to 22 bar. Appropriate pressure ensures a tight bond between the surface resin and the substrate, fully filling the interfacial gaps. Pressure below 15 bar results in insufficient interfacial contact and inadequate bonding strength; pressure above 25 bar is excessive and, even with a rigid core layer, may cause pressure damage to the optical fiber 5, and the substrate is prone to deformation.
[0062] The actual lamination process adopts a segmented heating and pressurization method. First, the temperature is raised to the surface melting temperature to degas the air, and then the pressure and temperature are gradually increased to the curing temperature. After curing, the film is slowly cooled to reduce residual stress inside the film and improve product reliability.
[0063] In some embodiments, the obtained optical fiber 5 is embedded in a flexible circuit board and then punched and metallized to obtain the electrical connection hole 4.
[0064] The present invention will be further illustrated by the following examples.
[0065] Example 1 This embodiment illustrates the fiber-embedded flexible circuit board and its fabrication method disclosed in this invention, including the following operations: Step 1: Preparation of polyacrylate core layer emulsion: A semi-continuous seed emulsion polymerization method was adopted. Sodium dodecyl sulfate emulsifier was dissolved in deionized water and stirred until completely dissolved. 49 parts of isoborneol methacrylate, 20 parts of cyclohexyl methacrylate, 12 parts of acrylonitrile, 3 parts of 1,6-hexanediol dimethacrylate, 6 parts of glycidyl methacrylate, 4 parts of methacrylic acid, and 3 parts of hexafluorobutyl methacrylate were mixed evenly and then slowly added to the emulsifier aqueous solution. The mixture was dispersed at high speed to obtain a pre-emulsion with a solid content of 43%. Add deionized water, 15% pre-emulsion and 25% ammonium persulfate initiator aqueous solution to the reaction vessel, stir and heat to 78°C, keep the temperature for 30 min to generate seed emulsion; Maintain the reaction temperature at 81℃, and simultaneously and uniformly add the remaining pre-emulsion and the remaining initiator aqueous solution for 4 hours; after the addition is complete, add 3 parts of γ-methacryloyloxypropyltrimethoxysilane to the system. After completion, the temperature was raised to 88℃ and maintained for 2 hours, then cooled to below 40℃. The pH was adjusted to 6.2 with ammonia, and the material was filtered to obtain a polyacrylate core layer emulsion. DMA testing showed that the glass transition temperature of the cured film was 172℃.
[0066] Step 2: Fabrication of the polyacrylate core layer with embedded optical fibers and elastic metal sheets: A polyacrylate core layer emulsion was coated on the surface of a PET release film and semi-dried at 90°C to form a 100μm thick semi-dry base film. Phosphorus-doped silica core / fluorine-doped silica cladding optical fibers (core diameter 50μm, cladding thickness 35μm) were arranged in parallel on the surface of the semi-dry base film with a channel spacing of 250μm. Beryllium bronze elastic metal sheets with a thickness of 20μm and a width of 100μm were laid in parallel at the same time, with the length direction of the elastic metal sheet parallel to the extension direction of the optical fiber. The polyacrylate core layer emulsion was then coated to completely encapsulate the optical fiber and the elastic metal sheet. After drying at 95°C, the film was pre-cured at 120°C for 30 minutes to obtain a polyacrylate core layer with a total thickness of 200μm and embedded with optical fiber and elastic metal sheet.
[0067] Step 3: Preparation of composite polyacrylate film: Polyacrylate surface emulsions were prepared using a semi-continuous seeded emulsion polymerization method, as follows: Sodium dodecyl sulfate emulsifier was dissolved in deionized water and stirred until completely dissolved. 50 parts of methyl methacrylate, 37 parts of isoborneol methacrylate, 4 parts of n-butyl acrylate, 5 parts of hydroxyethyl methacrylate, 3 parts of acrylic acid, and 1 part of trimethylolpropane triacrylate were mixed evenly and then slowly added to the emulsifier aqueous solution and dispersed at high speed to obtain a pre-emulsion with a solid content of 40%. Add deionized water, 15% pre-emulsion and 25% ammonium persulfate initiator aqueous solution to the reaction vessel, stir and heat to 78°C, keep the temperature for 30 min to generate seed emulsion; Maintain the reaction temperature at 80~82℃, and simultaneously and uniformly add the remaining pre-emulsion and the remaining initiator aqueous solution for 4 hours. After completion, the temperature was raised to 88℃ and maintained for 2 hours, then cooled to below 40℃. The pH was adjusted to 6.2 with ammonia, and the material was filtered to obtain a polyacrylate surface emulsion. DMA testing showed that the glass transition temperature of the cured film was 118℃.
[0068] Polyacrylate surface emulsion was coated on both the upper and lower surfaces of the polyacrylate core layer and dried with hot air at 90°C to remove moisture. The thickness of both surface layers was 25 μm, resulting in a composite polyacrylate film with a total thickness of 250 μm.
[0069] Step 4: Embedding optical fibers into flexible circuit boards and laminating them: The composite polyacrylate film is placed between the first flexible PI sub-board layer with a copper first circuit layer and the second flexible PI sub-board layer with a copper second circuit layer. It is then placed in a laminator and subjected to segmented heating and pressurization: first, the temperature is raised to 120°C and the air is vented for 5 minutes, then the pressure is raised to 20 bar, and the temperature is raised to 155°C and held for 40 minutes to cure. After slowly cooling to room temperature, the material is discharged. Through-hole electrical connection holes are processed at the positions that avoid the optical fiber and the elastic metal sheet. After the holes are metallized, the electrical connection between the upper and lower circuit layers is achieved, resulting in an optical fiber embedded flexible circuit board.
[0070] Example 2 This embodiment illustrates the fiber-embedded flexible circuit board and its fabrication method disclosed in this invention, including most of the operational steps in Embodiment 1, with the following differences: In the polyacrylate core emulsion formulation of step 1, hexafluorobutyl methacrylate was not added. After adjustment, 49 parts of isoborneol methacrylate and 23 parts of cyclohexyl methacrylate were used, and the remaining components and amounts were completely consistent with those in Example 1. The remaining preparation steps and structural parameters were the same as those in Example 1.
[0071] Example 3 This embodiment illustrates the fiber-embedded flexible circuit board and its fabrication method disclosed in this invention, including most of the operational steps in Embodiment 1, with the following differences: In step 2, no beryllium bronze elastic metal sheet is laid; only optical fibers are arranged, and the polyacrylate core layer only embeds the optical fiber structure. The remaining preparation steps and formulation parameters are the same as in Example 1.
[0072] Comparative Example 1 This comparative example is used to illustrate the fiber-embedded flexible circuit board disclosed in this invention, including most of the operational steps in Example 1, with the following differences: Instead of using a three-layer composite film structure, a single-layer film was prepared directly using the polyacrylate surface emulsion from Example 1. The optical fiber was directly embedded inside the single-layer film, with a total film thickness of 250 μm. The lamination process parameters were the same as in Example 1. That is, the conventional single-layer low-Tg polyacrylate film fiber embedding scheme of existing technology was adopted, without a high-Tg core layer support structure.
[0073] Comparative Example 2 This comparative example is used to illustrate the fiber-embedded flexible circuit board disclosed in this invention, including most of the operational steps in Example 1, with the following differences: Instead of using a three-layer composite film structure, a single-layer film was prepared directly using the polyacrylate core emulsion from Example 1. The optical fiber was directly embedded inside the single-layer film, with a total film thickness of 250 μm. The lamination process parameters were the same as in Example 1. This method employs a single-layer high-Tg polyacrylate film fiber embedding scheme, eliminating the need for a low-Tg bonding surface layer.
[0074] Comparative Example 3 This comparative example is used to illustrate the fiber-embedded flexible circuit board disclosed in this invention, including most of the operational steps in Example 1, with the following differences: In the polyacrylate core emulsion formulation of Step 1, the amount of high-Tg hard monomers was reduced and soft monomers were introduced, resulting in the following composition: 30 parts isoborneol methacrylate, 15 parts cyclohexyl methacrylate, 20 parts n-butyl acrylate, 8 parts acrylonitrile, 3 parts 1,6-hexanediol dimethacrylate, 6 parts glycidyl methacrylate, 4 parts methacrylic acid, 3 parts γ-methacryloyloxypropyltrimethoxysilane, and 3 parts hexafluorobutyl methacrylate. Testing showed that the glass transition temperature of this core layer after curing was 152°C, lower than the design lower limit of 165°C. The remaining preparation steps, surface structure, and lamination process were the same as in Example 1.
[0075] Performance testing The core performance indicators of the fiber-embedded flexible circuit board prepared above were selected for testing, with a focus on verifying the fiber protection effect during the hot pressing process, the reliability of interface bonding, and the long-term bending stability: Fiber position offset: The deviation between the actual spacing of the fiber channel after lamination and the designed spacing is measured using an optical microscope. Twenty channels are randomly selected from each sample for testing, and the maximum offset is taken. The unit is μm.
[0076] Fiber breakage rate: The continuity status of all fiber optic channels was detected using an optical time domain reflectometer (OTDR), and the proportion of broken fiber optic channels to the total number of channels was calculated, in units of %.
[0077] Interlayer peel strength: Refer to GB / T2792 standard to test the 90° peel strength between the adhesive film and the PI flexible sub-board, with the unit being N / cm.
[0078] Loss increment after bending cycle: The sample is bent 180° perpendicular to the fiber axis with a bending radius of 8 mm. After 1000 bending cycles, the optical insertion loss is tested, and the average loss difference before and after bending is calculated in dB.
[0079] Enter the test results into Table 1.
[0080] Table 1 As can be seen from the test results in Table 1, the three-layer composite structure of the present invention can simultaneously take into account both optical fiber protection and interlayer bonding performance during the hot pressing process, effectively solving the technical problem that a single-layer adhesive film cannot take into account both.
[0081] Comparing Example 1 with Comparative Example 1, it can be seen that the single-layer low-Tg adhesive film completely melts and flows during hot pressing, which cannot provide rigid support for the optical fiber, resulting in an optical fiber offset of over 60μm, a breakage rate of nearly 20%, and a significant increase in loss after bending; while the high-Tg core layer of the present invention can control the optical fiber offset within 10μm and prevent optical fiber breakage, thus significantly improving optical stability.
[0082] Comparing Example 1 and Comparative Example 2, it can be seen that although a single-layer high-Tg adhesive film can protect optical fibers, the interlayer peel strength is only 2.4 N / cm, and the bonding reliability is seriously insufficient, which cannot meet the requirements of actual use. The present invention improves the peel strength to more than 12 N / cm through the fusion bonding design of low-Tg surface layers on both sides, which meets the bonding standard of flexible circuit boards.
[0083] Comparing Example 1 and Comparative Example 3, it can be seen that when the core layer Tg is lower than the design lower limit of 165°C, the core layer softens at the lamination temperature, the support capacity decreases, and the risk of fiber misalignment and breakage increases significantly. This proves that the core layer Tg parameter is the core control indicator for achieving the effect of hot-pressed fiber protection.
[0084] Comparing Examples 1 and 2, it can be seen that when no fluorine-containing monomer is added to the core layer, the loss increment after bending cycles is more than doubled. This is because the fluorine-containing monomer can improve the interfacial wettability between the resin and the fluorine-doped silica fiber, and strengthen the interfacial bonding; without this component, micro-voids are easily generated at the interface during bending, leading to rapid accumulation of micro-bending loss.
[0085] Comparing Examples 1 and 3, it can be seen that without the embedded elastic metal sheet, the loss increment after bending is more than four times that of the preferred scheme. The elastic metal sheet can disperse bending stress and constrain the minimum bending radius, effectively reducing the micro-bending deformation of the optical fiber; without this structure, bending stress is concentrated, and long-term bending reliability is significantly reduced.
[0086] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A flexible circuit board with embedded optical fiber, characterized in that, The system includes a first flexible sub-board layer, a second flexible sub-board layer, and a composite polyacrylate film. The composite polyacrylate film is located between the first and second flexible sub-board layers. A first circuit layer is disposed on the surface of the first flexible sub-board layer facing the composite polyacrylate film, and a second circuit layer is disposed on the surface of the second flexible sub-board layer facing the composite polyacrylate film. The composite polyacrylate film includes an optical fiber, a polyacrylate core layer, a first polyacrylate surface layer, and a second polyacrylate surface layer. The polyacrylate core layer is film-shaped, and the optical fiber is embedded in the polyacrylate core layer. The first and second polyacrylate surface layers... The layers are located on both sides of the polyacrylate core layer. The glass transition temperature of the polyacrylate core layer is 165℃~178℃, the glass transition temperature of the first polyacrylate surface layer is 112℃~125℃, and the glass transition temperature of the second polyacrylate surface layer is 112℃~125℃. The polyacrylate core layer is formed by emulsion polymerization of monomer components comprising the following parts by weight, followed by thermal crosslinking and curing: 58~72 parts of high Tg hard monomer, 8~15 parts of acrylonitrile, 2~5 parts of 1,6-hexanediol dimethacrylate, 4~8 parts of epoxy functional monomer, 3~6 parts of carboxyl functional monomer, 2~4 parts of silane coupling monomer, and 2~4 parts of fluorine-containing monomer. The high Tg hard monomer includes one or more of isoborneol methacrylate and cyclohexyl methacrylate; the epoxy functional monomer is selected from glycidyl methacrylate; the carboxyl functional monomer is selected from methacrylic acid; the silane coupling monomer is selected from γ-methacryloyloxypropyltrimethoxysilane; and the fluorine-containing monomer is selected from hexafluorobutyl methacrylate.
2. The optical fiber embedded flexible circuit board according to claim 1, characterized in that, The optical fiber includes a core and a cladding. The cladding covers the outer periphery of the core. The core is phosphorus-doped quartz, and the cladding is fluorine-doped quartz. The diameter of the core is 10~70μm, and the thickness of the cladding is 20~60μm.
3. The optical fiber embedded flexible circuit board according to claim 1, characterized in that, The first polyacrylate surface layer and the second polyacrylate surface layer are each independently polymerized from monomer components comprising the following parts by weight: 45-55 parts of methyl methacrylate, 35-42 parts of isoborneol methacrylate, 3-6 parts of n-butyl acrylate, 4-6 parts of hydroxyethyl methacrylate, 2-4 parts of acrylic acid, and 0.5-1.5 parts of trimethylolpropane triacrylate.
4. The optical fiber embedded flexible circuit board according to claim 1, characterized in that, The thickness of the polyacrylate core layer is 100~300μm; the thickness of the first polyacrylate surface layer and the second polyacrylate surface layer are each 15~50μm; the optical fibers are arranged in a parallel array within the polyacrylate core layer, and the channel spacing between adjacent optical fibers is 127~5000μm.
5. The optical fiber embedded flexible circuit board according to claim 1, characterized in that, The composite polyacrylate film also includes an elastic metal sheet, which is embedded in the polyacrylate core layer in parallel with the optical fiber, and the length direction of the elastic metal sheet is parallel to the extension direction of the optical fiber. The optical fiber embedded in the flexible circuit board has an electrical connection hole that penetrates the first flexible sub-board layer, the composite polyacrylate film, and the second flexible sub-board layer. The electrical connection hole avoids the optical fiber and the elastic metal sheet and electrically connects the first circuit layer and the second circuit layer.
6. A method for fabricating an optical fiber embedded flexible circuit board according to any one of claims 1 to 5, characterized in that, Includes the following steps: S1. Polyacrylate core layer emulsion was prepared by semi-continuous seed emulsion polymerization. S2. Coat the release carrier surface with a polyacrylate core layer emulsion and semi-dry it with hot air to form a semi-dry base film; arrange the optical fibers in parallel on the surface of the semi-dry base film, then coat the optical fibers with a polyacrylate core layer emulsion to completely wrap the optical fibers, and pre-cur them after drying to obtain the polyacrylate core layer of the embedded optical fiber. S3. Coat the upper and lower surfaces of the polyacrylate core layer with polyacrylate surface emulsion, and dry with hot air to form a film to obtain a composite polyacrylate film. S4. The composite polyacrylate film is placed between the first flexible sub-board layer with the first circuit layer and the second flexible sub-board layer with the second circuit layer, and then placed in a laminator for heating and pressing to cure. After cooling, an optical fiber embedded flexible circuit board is obtained.
7. The preparation method according to claim 6, characterized in that, Step S1 specifically includes: Dissolve the emulsifier in deionized water and stir until completely dissolved; mix the high Tg hard monomer, acrylonitrile, 1,6-hexanediol dimethacrylate, epoxy functional monomer, carboxyl functional monomer and fluorine-containing monomer evenly and slowly add them to the emulsifier aqueous solution, and disperse at high speed to obtain a pre-emulsion with a solid content of 42%~45%. Add water, 10%~20% pre-emulsion and 20%~30% initiator aqueous solution to the reaction vessel, stir and heat to 78℃, keep the temperature for 20~40 min to generate seed emulsion; Maintain the reaction temperature at 80-82℃, and simultaneously and uniformly add the remaining pre-emulsion and the remaining initiator aqueous solution for 3.5-5 hours; after the addition is complete, add the silane coupling monomer to the system. After completion, heat to 85℃~90℃ and maintain for 1.5~3 hours, then cool to below 40℃, adjust pH to 6.0~6.5, and filter to obtain polyacrylate core layer emulsion.
8. The preparation method according to claim 6, characterized in that, In step S3, the polyacrylate surface emulsion is prepared by semi-continuous seed emulsion polymerization and has a solid content of 38%~42%; after coating, it is dried with hot air at 80~100℃ to remove moisture.
9. The preparation method according to claim 6, characterized in that, In step S4, the lamination pressure is controlled at 15~25 bar and the temperature is 150℃~160℃.